Re‐Emergence of Bluetongue Virus Serotype 8 in France, 2015. Issue 3 (30th November 2015) - Sailleau, C.; Bréard, E.; Viarouge, C.; Vitour, D.; Romey, A.; Garnier, A.; Fablet, A.; Lowenski, S.; Gorna, K.; Caignard, G.; Pagneux, C.; Zientara, S.
Summary: At the end of August 2015, a ram located in central France (department of Allier) showed clinical signs suggestive of BTV (Bluetongue virus) infection. However, none of the other animals located in the herd showed any signs of the Bluetongue disease. Laboratory analyses identified the virus as BTV serotype 8. The viro and sero prevalence intraherd were 2.4% and 8.6% in sheep and 18.3% and 42.9% in cattle, respectively. Phylogenetic studies showed that the sequences of this strain are closely related to another BTV‐8 strain that has circulated in France in 2006–2008. The origin of the outbreak is unclear but it may be assumed that the BTV‐8 has probably circulated at very low prevalence (possibly in livestock or wildlife) since its first emergence in 2007–2008.